Strategi Peningkatan Kinerja Kepolisian Dalam Memberikan Pelayanan Publik Di Kepolisian Sektor Galesong Kabupaten Takalar - Andira, Ayu; Razak, Rosdianti; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of the study was to determine the Strategy for Improving Police Performance in Providing Public Services in the Police Sector of Galesong, Takalar Regency. This study uses a qualitative method. Data collection techniques using observation, interviews, and documentation. The informants in the study consisted of 5 (five) people. The results of this study indicate that 1) the aspect of increasing Polri's motivation is carried out by providing examples and instilling a disciplined attitude to help improve Polri's performance, 2) welfare aspects for employees can encourage Polri's work spirit at the Galesong Police Station 3) aspects of a harmonious organizational climate, Galesong Polsek works with a close family system so that the work environment becomes safe and comfortable 4) leadership aspects at the Galesong Police are very supportive of improving performance with morning meetings and giving directions 5) career development aspects are very helpful for Polri in planning careers such as promotions and positions through education and training.  Keywords: Strategy, Performance, Public Service